MARCH1-mediated ubiquitination of MHC II impacts the MHC I antigen presentation pathway. - Kayla R Wilson; Haiyin Liu; Geraldine Healey; Vivian Vuong; Satoshi Ishido; Marco J Herold; Jose A Villadangos; Justine D Mintern (PLoS ONE, 2018)
Major histocompatibility complex class II (MHC II) expression and turn-over are regulated via its ubiquitination by the membrane associated RING-CH 1 (MARCH1) E3 ligase. Unexpectedly, we show that MHC II ubiquitination also impacts MHC I. Lack of MARCH1 in B cells and dendritic cells (DCs) resulted in a significant reduction in surface MHC I expression. This decrease was not directly caused by changes in MARCH1 ubiquitination of MHC I but indirectly by altered MHC II trafficking in the absence of its ubiquitination. Deletion of MHC II in March1-/- cells restored normal MHC I surface expression and replacement of wild type MHC II by a variant that could not be ubiquitinated caused a reduction in MHC I expression. Furthermore, these cells displayed inefficient presentation of peptide and protein antigen via MHC I to CD8+ T cells. In summary, we describe an unexpected intersection between MHC I and MHC II such that the surface expression of both molecules are indirectly and directly regulated by MARCH1 ubiquitination, respectively.